Foreign currencies exposures of Malaysia firms : does hedging strategy explain stock returns? - Chang, Hui Siang (Universiti Malaysia Sarawak (UNIMAS), 2011)
The purpose of this study is to investigate exporter’s currencies exposures in Malaysia listed firms. The study also attempt to determine the relationship between the stock returns of Malaysia listed firms and the foreign currencies exposures’ portfolio (USD, SGD, THB, JPY, POUND, and EURO). The sample consists of 241 listed firms from 2008 to 2009. Out of 947 firms, 241 firms have foreign currencies exposures on USD (7.1 billion), SGD (1.2 billion), THB (72 billions), JPY (22 million), POUND (0.1 billion) and EURO (0.3 billion) for two years. This analysis based on account receivables for foreign currencies exposures and significant level of MYR appreciation and depreciation on the stock returns. The results reveal that the USD currency portfolio is the most dominant source of foreign currencies exposures, this followed by SGD, EURO, THB, POUND and JPY. In contrast, the main findings show that the EURO currency portfolio is the most significant source of currency exposure risk that will increase the firms’ returns when MYR/EURO appreciate, which is opposite to our expectations. Despite that, USD currency portfolio is insignificant contribute to the firms’ return. Nevertheless, the study finds that hedging play an important role. A larger firm with hedging on USD is found to increase stock returns when MYR depreciate 1 per cent against USD, which is benefited the exporters. The results were opposite if the exporter firms do not apply hedging contracts on foreign currencies. Overall, hedging strategy is found to be an effecting tool to reduce risk of USD exposures.